Soma to germline inheritance of extrachromosomal genetic information via a LINE‐1 reverse transcriptase‐based mechanism. (17th June 2016) - Spadafora, Corrado
Abstract : Mature spermatozoa are permeable to foreign DNA and RNA molecules. Here I propose a model, whereby extrachromosomal genetic information, mostly encoded in the form of RNA in somatic cells, can cross the Weismann barrier and reach epididymal spermatozoa. LINE‐1 retrotransposon‐derived reverse transcriptase (RT) can play key roles in the process by expanding the RNA‐encoded information. Retrotransposon‐encoded RT is stored in mature gametes, is highly expressed in early embryos and undifferentiated cells, and becomes downregulated in differentiated cells. In turn, RT plays a role in developmental control, as its inhibition arrests developmental progression of early embryos with globally altered transcriptomic profiles. Thus, sperm cells act as recipients, and transgenerational vectors of somatically derived genetic information which they pass to the next generation with the potential to modify the fate of the developing embryos. Abstract : Non‐Mendelian transgenerational inheritance is a growingly recognized phenomenon, yet elusive in molecular terms. I propose that RNA‐based information released from somatic cells can cross the Weismann barrier, be internalized in epididymal spermatozoa which mediate the acquisition of new traits in the embryos at fertilization. Sperm endogenous reverse transcriptase plays key roles in the process.